Protective Effects of Intestinal Gallic Acid in Neonatal Dairy Calves Against Extended-Spectrum β-lactamase Producing Enteroaggregative Escherichia coli Infection: Modulating Intestinal Homeostasis and Colitis - He, Zhiyuan; Ma, Yulin; Chen, Xu; Liu, Shuai; Xiao, Jianxin; Wang, Yajing; Wang, Wei; Yang, Hongjian; Li, Shengli; Cao, Zhijun (Frontiers in Nutrition, 2022)
Calf diarrhea induced by enteroaggregative E. coli (EAEC) is spreading fast among young ruminants, causing continuous hazard to dairy industry. Antimicrobial drug abuse aggravates the incidence rate of multi-drug resistant (MDR) extended-spectrum β-lactamase producing E. coli (ESBL-EC). However, knowledge of detection and significance of disease-related biomarkers in neonatal female calves are still limited. Gallic acid (GA), a natural secondary metabolite mostly derived from plants, has attracted increasing attention for its excellent anti-inflammatory and anti-oxidative properties. While, it is vague how GA engenders amelioration effects on clinical symptoms and colitis induced by ESBL-EAEC infection in neonatal animals. Here, differentiated gut microbiome and fecal metabolome discerned from neonatal calves were analysed to ascertain biomarkers in their early lives. Commensal Collinsella and Coriobacterium acted as key microbial markers mediating colonization resistance. Besides, there existed strongly positive relation between GA, short-chain fatty acid (SCFA), or other prebiotics and those commensals using random forest machine learning algorithm and Spearman correlation analyses. The protective effect of GA pretreatment on bacterial growth, cell adherence, and ESBL-EAEC-lipopolysaccharide (LPS) treated Caco-2 cells were first assessed and results revealed direct antibacterial effects and diminished colonic cell inflammation. Then, oral GA mediated colitis attenuation and recovery of colonic short-chain fatty acid (SCFA) productions on neonatal mice peritonitis sepsis or oral infection model. To corroborate this phenomenon, fecal microbiota transplantation (FMT) method was adopted to remedy the bacterial infection. Of note, FMT from GA-treated neonatal mice achieved profoundly remission of clinic symptoms and colitis over the other groups as demonstrated by antibacterial capability and prominent anti-inflammatory abilities, revealing by improved hindgut microbiota structure with enriched Clostridia_UCG-014, Lachnospiraceae, Oscillospiraceae, and Enterococcaceae, and upregulation of SCFA productions. Collectively, our findings provided the direct evidences of hindgut microbiota and intestinal metabolites discriminating the health status of neonatal calves post ESBL-EAEC infection. The data provided novel insights into GA-mediated remission of colitis via amelioration of hindgut commensal structure and upregulation of SCFA productions, and its eminent role as potential antibiotic alternative or synergist for future clinic ESBL-EAEC control in livestock.